Influence Of Personality And Spirituality On Job Satisfaction And Organizational Commitment Among Employees From The Hotel Industry In Penang: The Role Of Gender And Ethnicity - Mathavan, Hemalatha (2023)
Personality traits and spirituality have a positive influence on job satisfaction and organizational commitment. Many studies on job satisfaction and organizational commitment have been conducted, yet studies focusing on the relationship between personality traits and spirituality are still scarce, especially in the hotel industry. Therefore, the present study aimed to determine whether personality and spirituality predict job satisfaction and organizational commitment among employees from the hotel industry in Penang. It further aimed to explore whether there are gender and ethnic differences in personality traits, spirituality, job satisfaction, and organizational commitment. The quantitative method with a cross-sectional design was used and 300 employees from three, four- and five-star hotels in Penang were recruited by stratified random sampling. The participants were given a questionnaire to fill out via their human resource department. The questionnaire comprised four instruments including Mini International Personality Item Poll, Spirit at Work Scale, Minnesota Satisfaction Questionnaire, and Affective Organizational Commitment. Standard multiple regression revealed that spirituality and personality traits of extraversion and agreeableness were significant predictors of job satisfaction. On the other hand, extraversion, conscientiousness, and spirituality significantly predicted organizational commitment.